Clickable SBA-15 mesoporous materials: synthesis, characterization and their reaction with alkynes - Malvi, Bharmana; Sarkar, Bibhas R.; Pati, Debasis; Mathew, Renny; Ajithkumar, Thalasseril G.; Sen Gupta, Sayam (Journal of Materials Chemistry, 2009)
SBA-15 mesoporous silica has been functionalized with azidopropyl groups through both one-pot co-condensation and post-synthetic grafting. For both these methodologies, azidopropyltriethoxysilane was used to introduce the azidopropyl groups. The azidopropyl modified SBA-15 material synthesized by one-pot co-condensation had hexagonal crystallographic order, pore diameters up of 50 angstrom, and the content of azidopropyl groups was found to be 1.3 mmol g(-1). The presence of the azidopropyl group was confirmed by multinuclear ((13)C, (29)Si) solid state NMR and IR spectroscopy. Both these materials underwent very efficient Cu(I)-catalyzed azide alkyne ``click'' reaction (CuAAC) with a variety of alkynes. Nearly 85% of the azide present in the SBA-15 material was converted to the corresponding triazole when propargyl alcohol was used as the substrate. This methodology was also used to incorporate mannose into SBA-15. Incubation of this mannose labeled SBA-15 with fluorescein labeled Concanavalin-A led to the formation of a fluorescent silica-protein hybrid material. The ease of synthesis for the azide labeled SBA-15 material together with its ability to undergo very efficient chemoselective CuAAC in water would make it a very attractive platform for the development of covalently anchored catalysts, enzymes and sensors.

Synthesis of glycopolypeptides by the ring opening polymerization of O-glycosylated-alpha-amino acid N-carboxyanhydride (NCA) - Pati, Debasis; Shaikh, Ashif Y.; Hotha, Srinivas; Sen Gupta, Sayam (Polymer Chemistry, 2011)
The novel synthesis of O-glycosylated lysine-NCA from a stable glycosyl donor and a commercially available protected amino acid in very high yield is reported. These O-glycosylated lysine-NCA monomers underwent ring opening polymerization using simple primary amine initiators to form well defined, high molecular weight homoglycopolypeptides and diblock co-glycopolypeptides. The synthesis of azide labelled end functionalized glycopolypeptides and amphiphilic diblock copolypeptides is also reported. This methodology represents an easy and practical route to the synthesis of O-glycosylated polypeptides with 100% glycosylation.

Controlled synthesis of O-glycopolypeptide polymers and their molecular recognition by lectins - Pati, Debasis; Shaikh, Ashif Y.; Das, Soumen; Nareddy, Pavan Kumar; Swamy, Musti J.; Hotha, Srinivas; Sen Gupta, Sayam (Biomacromolecules, 2012)
The facile synthesis of high molecular weight water-soluble O-glycopolypeptide polymers by the ring-opening polymerization of their corresponding N-carboxyanhydride (NCA) in very high yield (overall yield > 70%) is reported. The per-acetylated-O-glycosylated lysine-NCA monomers, synthesized using stable glycosyl donors and a commercially available protected amino acid in very high yield, was polymerized using commercially available amine initiators. The synthesized water-soluble glycopolypeptides were found to be alpha-helical in aqueous solution. However, we were able to control the secondary conformation of the glycopolypeptides (alpha-helix vs nonhelical structures) by polymerizing raceznic amino acid glyco NCAs. We have also investigated the binding of the glycopolypeptide poly(alpha-manno-O-lys) with the lectin Con-A using precipitation and hemagglutination assays as well as by isothermal titration calorimetry (ITC). The ITC results clearly show that the binding process is enthalpy driven for both alpha-helical and nonhelical structures, with negative entropic contribution. Binding stoichiometry for the glycopolypeptide poly(alpha-manno-O-lys) having a nonhelical structure was slightly higher as compared to the corresponding polypeptide which adopted an alpha-helical structure.

Multiple topologies from glycopolypeptide-dendron conjugate self-assembly: nanorods, micelles, and organogels - Pati, Debasis; Kalva, Nagendra; Das, Soumen; Kumaraswamy, Guruswamy; Sen Gupta, Sayam; Ambade, Ashootosh V. (Journal of the American Chemical Society, 2012)
Glycopolypeptides (GPs) were synthesized by ring-opening polymerization of glycosylated N-carboxyanhydride monomer and attached to hydrophobic dendrons at one chain end by ``click'' reaction to obtain amphiphilic anisotropic macromolecules. We show that by varying polypeptide chain length and dendron generation, an organogel was obtained in dimethylsulfoxide, while nanorods and micellar aggregates were observed in aqueous solutions. Assemblies in water were characterized by electron microscopy and dye encapsulation. Secondary structure of the GP chain was shown to affect the morphology, whereas the chain length of the poly(ethylene glycol) linker between the GP and dendron did not alter rod-like assemblies. Bioactive surface chemistry of these assemblies displaying carbohydrate groups was demonstrated by interaction of mannose-functionalized nanorods with ConA.

Synthesis and self-assembly of glycopolypeptides - Pati, Debasis; Sen Gupta, Sayam (Abstracts of Papers of the American Chemical Society, 2012)

Synthesis of silk fibroin-glycopolypeptide conjugates and their recognition with lectin - Das, Soumen; Pati, Debasis; Tiwari, Neha; Nisal, Anuya; Sen Gupta, Sayam (Biomacromolecules, 2012)
Silk fibroin (SF), the natural fibrous protein created by the Bombyx mori silk worm, is being increasingly excellent mechanical strength, high oxygen/water permeability, excellent mechanical strength; high oxygen/water:permeability, and biocompatibility: :It is also well known that surface. modification of SF, With Organic ligands such as the extracellular protein :binding. Arg-Gly-Asp, (RGD) peptides:,: help adhesion and,proliferation. of cells better-a key; requirement for it to function as extracellular. matrices; In this, Work, We have conjugated synthetic glycopolypeptides (GPs) that were synthesized by controlled ring opening polymerization of alpha-manno-lys N-carboxyanhydrides (NCAs) onto SF by using Cu catalyzed click reaction to synthesize 1 a new hybrid :Material (SF GP), Which We believe will have :both the mechanical properties of native SF and the molecular recognition property of the carbohydrates in the GP. By controlling the :amount of GP grafted onto SF, we have made three SF GP conjugates that differ in their ability to assemble into films. SF GP conjugates having a very high content of GP formed completely water soluble brush like polymer that displayed very high affinity toward the lectin concanavalin-A (Con-A) Films cast from SF-GP conjugates using lower amounts of grafted GP were more stable in water, and the stability can be modulated by varying the amount of G grafted. The water insoluble film SF-GP(25) was also found to bind to fluorescently labeled Con A, as was seen by confocal microscopy Such SF-GP hybrid films may be useful as mimics of extracellular matrices for tissue engineering:

Cationic charged helical glycopolypeptide using ring opening polymerization of 6-deoxy-6-azido-glyco-N-carboxyanhydride - Shaikh, Ashif Y.; Das, Soumen; Pati, Debasis; Dhaware, Vinita; Sen Gupta, Sayam; Hotha, Srinivas (Biomacromolecules, 2014)
Glycopolypeptides with a defined secondary structure are of significance in understanding biological phenomena. Synthetic glycopolypeptides, or polypeptides featuring pendant carbohydrate moieties, have been of particular interest in the field of tissue engineering and drug delivery. In this work, we have synthesized charged water-soluble glycopolypeptides that adopt a helical conformation in water. This was carried out by the synthesis of a glyco-N-carboxyanhydride (glyco-NCA) containing an azide group at the sixth position of the carbohydrate ring. Subsequently, the NCA was polymerized to obtain azide-containing glycopolypeptides having good control over molecular weight and polydispersity index (PDI) in high yields. We were also able to control the incorporation of the azide group by synthesizing random co-glycopolypeptide containing 6-deoxy-6-azido and regular 6-OAc functionalized glucose. This azide functionality allows for the easy attachment of a bioactive group, which could potentially enhance the biological activity of the glycopolypeptide. We were able to obtain water-soluble charged glycopolypeptides by both reducing the azide groups into amines and using CuAAC with propargylamine. These charged glycopolypeptides were shown to have a helical conformation in water. Preliminary studies showed that these charged glycopolypeptides showed good biocompatibility and were efficiently taken up by HepG2 cells.

Tunable nanocarrier morphologies from glycopolypeptide-based amphiphilic biocompatible star copolymers and their carbohydrate specific intracellular delivery - Pati, Debasis; Das, Soumen; Patil, Naganath G.; Parekh, Nimisha; Anjum, Dalaver H.; Dhaware, Vinita; Ambade, Ashootosh V.; Sen Gupta, Sayam (Biomacromolecules, 2016)
Nanocarriers with carbohydrates on the surface represent a very interesting class of drug-delivery vehicles because carbohydrates are involved in biomolecular recognition events in vivo. We have synthesized biocompatible miktoarm star copolymers comprising glycopolypeptide and poly(e-caprolactone) chains using ring-opening polymerization and ``click chemistry''. The amphiphilic copolymers were self-assembled in water into morphologies such as nanorods, polymersomes, and micelles with carbohydrates displayed on the surface. We demonstrate that the formation of nanostructure could be tuned by chain length of the blocks and was not affected by the type of sugar residue. These nanostructures were characterized in detail using a variety of techniques such as TEM, AFM, cryogenic electron microscopy, spectrally resolved fluorescence imaging, and dye encapsulation techniques. We show that it is possible to sequester both hydrophobic as well as hydrophilic dyes within the nanostructures. Finally, we show that these noncytotoxic mannosylated rods and polymersomes were selectively and efficiently taken up by MDA-MB-231 breast cancer cells, demonstrating their potential as nanocarriers for drug delivery.